Comparison of percutaneous coronary intervention vs coronary artery bypass graft for left main coronary artery disease in patients with prior cerebrovascular disease: A systematic review, meta-analysis and meta-regression - Muhammad Hamza Shuja; Firzah Shakil; Syed Hassaan Ali; Qazi Shurjeel Uddin; Ayesha Noman; Javed Iqbal; Muhammad Ahmed; Faiza Sajid; Haya Waseem Ansari; Syed Ahmed Farhan; Huzaifa Ul Haq Ansari; Syed Husain Farhan; et al. (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Previous studies suggest similar cardiovascular (CV) benefits for either percutaneous coronary intervention (PCI) or coronary artery bypass graft (CABG) in patients with left main coronary artery disease (LMCAD). However, limited data exist on the influence of prior cerebrovascular disease (CEVD). Thus, we aim to compare the CV outcomes in patients with LMCAD and prior CEVD, undergoing either PCI or CABG. Methods: A comprehensive search from (January 2000 to August 2024) identified three relevant studies. Outcomes analyzed included all-cause mortality, major adverse cardiac and cerebrovascular events (MACCE), myocardial infarction (MI), and risk of stroke in patients undergoing either PCI or CABG for LMCAD. Data analysis employed a random effects model and presented hazard ratios (HR) along with their 95 % confidence intervals (CI). Results: Three studies involving 760 patients (361 PCI, 399 CABG) were included. PCI was associated with a significantly higher risk of MACCE (HR = 2.56; 95 % CI = 1.23–5.37; p = 0.01; I2 = 86 %) and MI (HR = 2.97; 95 % CI = 1.72–5.13; p < 0.0001; I2 = 0 %) compared to CABG. No significant differences were observed in all-cause mortality (HR = 1.35; 95 % CI = 0.92–1.98; p = 0.12; I2 = 0 %) or recurrent stroke (HR = 0.83; 95 % CI = 0.40–1.70; p = 0.60; I2 = 1 %). The risk of repeat revascularization was higher in PCI, though not statistically significant (HR = 3.44; 95 % CI = 0.50–23.60; p = 0.21; I2 = 70 %). Conclusion: PCI significantly elevates the risk of MACCE and MI in patients with LMCAD and prior CEVD compared to CABG. However, risks of all-cause mortality, repeat stroke, and revascularization were non-significant. Comorbidities may drive the elevated risk, underscoring the need for tailored strategies in this population.